PENGARUH KEPEMIMPINAN, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD PEMERINTAH KABUPATEN SERDANG BEDAGAI - Elvie Maria; May Handri; Purnama Sari (Universitas Methodist Indonesia, 2018)
The purpose of this study is to examine the effect of leadership and work discipline on employee performance at Sekretariat DPRD Pemerintah Kabupaten Serdang Bedagai. The population in this study were all employees totaling 62 people and all of them became the respondents. The research method used is quantitative descriptive. The results of the study state that the contribution of leadership and work discipline towards employee performance is 64.2%, and explained that leadership and work discipline simultaneously have a significant effect on the employee’s performance.